The influence of a tomato food matrix on the bioavailability and plasma kinetics of oral gamma-aminobutyric acid (GABA) and its precursor glutamate in healthy men. Issue 16 (19th July 2022) - de Bie, Tessa H.; Balvers, Michiel G. J.; de Vos, Ric C. H.; Witkamp, Renger F.; Jongsma, Maarten A.
Abstract : The pureed tomato food matrix does not affect the bioavailability of gamma-aminobutyric acid, while glutamate from tomatoes is absorbed slower, and with a lower peak concentration, relative to a solution in water. Abstract : Gamma-aminobutyric acid (GABA) and its precursor glutamate play signaling roles in a range of tissues. Both function as neurotransmitters in the central nervous system, but they also modulate pancreatic and immune functioning, for example. Besides endogenous production, both compounds are found in food products, reaching relatively high levels in tomatoes. Recent studies in rodents suggest beneficial effects of oral GABA on glucose homeostasis and blood pressure. However, the bioavailability from food remains unknown. We studied the bioavailability of GABA and glutamate from tomatoes relative to a solution in water. After a fasting blood sample was taken, eleven healthy men randomly received 1 liter of 4 different drinks in a cross-over design with a one-week interval. The drinks were a solution of 888 mg L −1 GABA, a solution of 3673 mg L −1 glutamate, pureed fresh tomatoes and plain water as the control. Following intake, 18 blood samples were taken at intervals for 24 hours. Plasma GABA and glutamate concentrations were determined by ultra-pressure liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS). Fasting plasma GABA and glutamate concentrations were found to be 16.71 (SD 2.18) ng mL −1 and 4626 (SD 1666) ng mL −1, respectively. Fasting GABA levels were constant (5.8 CV%) between individuals, while fasting glutamate levels varied considerably (23.5 CV%). GABA from pureed tomatoes showed similar bioavailability to that of a solution in water. For glutamate, the absorption from pureed tomatoes occurred more slowly as seen from a longer t max (0.98 ± 0.14 h vs. 0.41 ± 0.04 h, P = 0.003) and lower C max (7815 ± 627 ng mL −1 vs. 16 420 ± 2778 ng mL −1, P = 0.006). These data suggest that GABA is bioavailable from tomatoes, and that food products containing GABA could potentially induce health effects similar to those claimed for GABA supplements. The results merit further studies on the bioavailability of GABA from other food products and the health effects of GABA-rich diets. The clinical trial registry number is NCT04086108 (; https://clinicaltrials.gov/ct2/show/NCT04303468 ).